2016
DOI: 10.15193/zntj/2016/104/097
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin � structure, properties, and application possibilities in functional food

Abstract: Astaksantyna jest ksantofilem naturalnie występującym w przyrodzie. Nadaje charakterystyczne różowo-czerwone zabarwienie tkankom ryb, takim jak łosoś i pstrąg, a także skorupom skorupiaków. Zwierzęta i ludzie nie przejawiają zdolności syntetyzowania astaksantyny de novo. Zdolność tę wykazują niektóre algi, drożdże, bakterie i rośliny. Dzięki budowie chemicznej astaksantyna charakteryzuje się silnymi właściwościami antyoksydacyjnymi. Jest uważana za jeden z najsilniejszych naturalnych antyoksydantów. Jak wynika… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…AST enters the blood and tissues, crossing the blood-brain barrier [220,221]. In vivo studies in rats showed no accumulation of AST in tissues [222,223], and the mean half-life is up to 52 h [219]. Naturally, ASTs occur in the form of stereoisomers (3S, 3 ′ S) and (3R, 3 ′ R), geometric isomers, and in free and esterified forms [214].…”
Section: Astaxanthinmentioning
confidence: 99%
See 1 more Smart Citation

Skin Protection by Carotenoid Pigments

Flieger,
Raszewska-Famielec,
Radzikowska-Büchner
et al. 2024
IJMS
“…AST enters the blood and tissues, crossing the blood-brain barrier [220,221]. In vivo studies in rats showed no accumulation of AST in tissues [222,223], and the mean half-life is up to 52 h [219]. Naturally, ASTs occur in the form of stereoisomers (3S, 3 ′ S) and (3R, 3 ′ R), geometric isomers, and in free and esterified forms [214].…”
Section: Astaxanthinmentioning
confidence: 99%
“…AST enters the blood and tissues, crossing the blood-brain barrier [220,221]. In vivo studies in rats showed no accumulation of AST in tissues [222,223], and the mean half-life is up to 52 h [219].…”
Section: Astaxanthinmentioning
confidence: 99%

Skin Protection by Carotenoid Pigments

Flieger,
Raszewska-Famielec,
Radzikowska-Büchner
et al. 2024
IJMS